Representation of The Indonesian President Candidate Leadership At Cnnindonesia.Com - Yulia Sofiani Zaimar; Ajeng Dinar Wisesa Wardhani (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2019)
In this research, the researchers examine the importance of the role of the media in shaping public opinion about an event, the framework of a media in the dissemination of information determines the information products produced from the media. The researchers would like to examine and to investigate the attitudes and ideas conveyed by non-verbal forms, contained in media. Political leadership constitutes a discourse, that must always be included in all political discussions, during the presidential election, including in the upcoming 2019 presidential election in Indonesia. In reality, the democratic political leadership criterias are not simply established, especially in the face of two things: the first is the existence of local values in which each country has the criterion of distinctive political leadership that sometimes contradicts the principles of democracy. In the Indonesian context. In this research, the researchers intended to use the theory used, namely the theory behind the Critical Discourse Analysis (CDA) method, comes from Foucault, relating to what happens in society, in what Harbermas Jurgen had explained.Key word: media, opinion, discourse, politic, election